2010
DOI: 10.1248/bpb.33.1394
|View full text |Cite
|
Sign up to set email alerts
|

Permeation Pathway of Macromolecules and Nanospheres through Skin

Abstract: The permeation pathway of macromolecules and nanospheres through skin was evaluated using fluorescent isothiocyanate (FITC)-dextran (average MW, 4 kDa) (FD-4) and nanospheres (500 nm in diameter) in hairless rat abdominal skin and porcine ear skin as well as a three-dimensional cultured human skin model (cultured skin model). A low molecular hydrophilic compound, sodium fluorescein (FL) (MW, 376 Da), was used for comparison. FL penetrated the stratum corneum and permeated the viable epidermis of hairless rat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…The reduction ratio of permeability coefficients by hair follicle-plugging for 99.5% EtOH was slightly lower than that for 0% or 20% EtOH because of the intrinsically very low permeabilities of FL and FD-4 for 99.5% EtOH. We previously reported that FL and FD-4 permeabilities through three-dimensional cultured skin were markedly lower than those through hairless rat skin, 28) and concluded that this may have been due to the absence of appendages in the cultured skin. The results of the present study, in which FL and FD-4 preferentially permeated through skin appendages, support our previous conclusion.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The reduction ratio of permeability coefficients by hair follicle-plugging for 99.5% EtOH was slightly lower than that for 0% or 20% EtOH because of the intrinsically very low permeabilities of FL and FD-4 for 99.5% EtOH. We previously reported that FL and FD-4 permeabilities through three-dimensional cultured skin were markedly lower than those through hairless rat skin, 28) and concluded that this may have been due to the absence of appendages in the cultured skin. The results of the present study, in which FL and FD-4 preferentially permeated through skin appendages, support our previous conclusion.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies on the transdermal deliveries of hydrophilic compounds have been performed using excised skin. 28,40,42,43,45,49) Evaluations of skin permeation parameters using excised skin are very useful for developing transdermal formulations. The skin permeation ratios of drugs through hair follicles against those through the whole permeation area should be considered to clarify the contribution of the hair follicle route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hair follicles are known to be an effective topical drug delivery route for hydrophilic drug and particles, despite the surface area of skin occupied by hair follicles is only about 0.1% of the total skin surface area. 31,32 Recently, follicular penetration of nano-and microparticle has been investigated and showed hair follicles as a primary penetration route for the particle-based deliver system containing macromolecules, chemical drug, vaccine. [33][34][35] The penetration depth depends on the size of the particles and the result isn't very similar because of difference in lipid type, combination of lipid, preparation methods.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Todo et al reported that polystyrene latex nanoparticles (mean particle size 500 nm) penetrated into the hair follicles of porcine skin. 32) On the other hand, Tahara et al reported that a S/O nanosuspension of protein (mean particle size: 214-257 nm) penetrated into the stratum corneum in the in vitro Yucatan micropig skin permeation experiments.…”
Section: )mentioning
confidence: 99%